2017
DOI: 10.1111/apt.14331
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory ascites with an automated low‐flow ascites pump in patients with cirrhosis

Abstract: SummaryBackgroundRefractory ascites (RA) is a frequent complication of cirrhosis, requiring large volume paracentesis or placement of a transjugular intrahepatic portosystemic shunt (TIPSS). The automated low‐flow ascites pump (alfapump, Sequana Medical AG, Zurich, Switzerland) is an innovative treatment option for patients with RA.AimTo assess safety and efficacy of this treatment in patients with a contraindication to TIPSS.MethodsFifty‐six patients (43 males; mean age 62 years) from centres in Germany, Swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 36 publications
(55 reference statements)
2
42
1
1
Order By: Relevance
“…For the 17 patients who required an LVP during the study, the time to the first LVP after alfapump implantation was delayed to more than 3 months, consistent with other reports of alfapump use in the literature . The majority of the postimplantation LVPs were related to pump or catheter malfunction, which is higher than in published studies .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For the 17 patients who required an LVP during the study, the time to the first LVP after alfapump implantation was delayed to more than 3 months, consistent with other reports of alfapump use in the literature . The majority of the postimplantation LVPs were related to pump or catheter malfunction, which is higher than in published studies .…”
Section: Discussionsupporting
confidence: 83%
“…This is the first North American study using the alfapump as a management tool for recurrent ascites. Like the previous European studies, we encountered a significant number of technical issues, and bacterial infections occurred in at least 40% of the study patients. Despite this, we demonstrated that the insertion of the alfapump system was effective in reducing the requirement for LVP.…”
Section: Discussionmentioning
confidence: 86%
“…The ALFApump ® involves an implantable device pumping ascites from the peritoneal cavity into the bladder . Consistent with the initial European multicentre safety and efficacy study and the multicentre RCT, recent studies have corroborated complication rates of infections (11%‐56%), renal dysfunction (21%‐67%), device deficiency including catheter occlusion (9%‐33%) and explantation rates of up to 30% . Recent NICE guidance on the ALFApump ® advises use only with ‘special arrangements’ and in research settings…”
Section: Discussionmentioning
confidence: 71%
“…We screened 309 references; 40 were selected for full‐text retrieval. Of these, nine were included in the analysis …”
Section: Resultsmentioning
confidence: 99%
“…Of these, nine were included in the analysis. 5,6,12,[20][21][22][23][24][25] Seven studies were published as full-text articles 5,6,12,[20][21][22][23] and two in abstract form. 24,25 With the exception of one randomised controlled trial, 6 all other studies were case series; only patients treated with automated low-flow ascites pump were considered in the meta-analysis (…”
Section: Discussionmentioning
confidence: 99%